The 1st International Electronic Conference on Microbiology 2021
DOI: 10.3390/proceedings2020066026
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Drug-Resistant Vibrio Cholerae Responsible for Cholera Outbreak among Migrant Domestic Workers in Kerala, South India

Abstract: Cholera outbreaks are prevalent in countries with a low Human Development Index (HDI) where people have limited access to safe drinking water, sanitation and hygiene (WASH). Intriguingly, the state of Kerala which records the highest HDI in India is endemic to cholera. We discuss the epidemiology of a cholera outbreak reported among migrant workers of Kerala in 2017. Virulence genes of Vibrio cholerae, toxR and ctxA, were detected in the river and ground water samples collected from the outbreaks sites which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Multi Drug-Resistance [MDR] was demonstrated by all the V. cholerae isolated from CRS environment though this was at varying degrees. The resistance recorded in the present study against SP, CPX, FEF], and OFX, is in line with the report given by Krishna et al [30], who also noted that V. cholerae isolates showed resistance against quinolones like Nalidixic, norfloxacin, Gatifloxacin, Moxifloxacin as well as gentamicin; a macrolide whose resistance has not been reported so easily. Also, MDR was observed in this study against Septrin [SXT] and Hydroxy-ampicillin [AM], streptomycin [S].…”
Section: Discussionsupporting
confidence: 93%
“…Multi Drug-Resistance [MDR] was demonstrated by all the V. cholerae isolated from CRS environment though this was at varying degrees. The resistance recorded in the present study against SP, CPX, FEF], and OFX, is in line with the report given by Krishna et al [30], who also noted that V. cholerae isolates showed resistance against quinolones like Nalidixic, norfloxacin, Gatifloxacin, Moxifloxacin as well as gentamicin; a macrolide whose resistance has not been reported so easily. Also, MDR was observed in this study against Septrin [SXT] and Hydroxy-ampicillin [AM], streptomycin [S].…”
Section: Discussionsupporting
confidence: 93%
“…The multiple antibiotic resistance seen among the E. coli isolates also underlines the anthropogenic role on the prevalence of fecal contaminants in the lake. Similar resistance patterns of bacteria have been reported from elsewhere, mostly from clinical isolates, veterinary sources, and sewage treatment systems. The resistance among the majority of isolates (>60%) to Erythromycin, Gentamicin, and Moxifloxacin found in this study is not surprising as a similar resistance to these antibiotics has been reported earlier in E. coli isolated from both clinical and environmental sources from various locations and is attributed to the common use of these antibiotics. However, resistance to the Carbapenem class of antibiotics (Meropenem) among a small number (<10%) of isolates is a matter of concern, as estuaries can function as a medium for gene exchange and increase the risk of spreading antibiotic-resistant bacteria in the environment and then back to humans . These high levels of multiple antibiotic resistance, combined with a high prevalence of E. coli in the lake waters, points to the importance of containing this contamination.…”
Section: Resultssupporting
confidence: 86%
“…Recent studies have reported compromised drug susceptibility pattern of V. cholerae O1 against newer drugs, including those which are not commonly used for the treatment of cholera [ 41 , 42 , 45 ]. For example, recently isolated V. cholerae O1 strains were reported to be resistant against extended spectrum beta-lactam antibiotics, such as the fourth generation cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recently isolated V. cholerae O1 strains were reported to be resistant against extended spectrum beta-lactam antibiotics, such as the fourth generation cephalosporins. Although the underlying molecular mechanism for the drug resistance is yet to be elucidated, it is presumed to be attributed to the activity of either extended spectrum of β-lactamase (ESBL) or AmpC β-lactamase [ 41 , 45 ]. Beta-Lactams are broad-spectrum drugs used to treat a wide range of infectious diseases and in post-operative infection management [ 46 ].…”
Section: Discussionmentioning
confidence: 99%